Aksesibilitas dan Rasa Keadilan Siswa Berkebutuhan Khusus di SMP Negeri 15 Semarang - Aqila Jihan Pradina Paramitha; Yan Amal Abdilah; Agustinus Sugeng Priyanto (CV. Alim's Publishing, 2026)
Inclusive education seeks to ensure that all learners, including students with special needs, have equal access to quality educational services. Its successful implementation depends on accessibility and educational fairness, which enable students to participate meaningfully in the learning process. This study examined the implementation of these two aspects at SMP Negeri 15 Semarang using a qualitative descriptive approach. Data were gathered through observations, interviews, and documentation involving the principal, teachers, and students with special needs, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that accessibility has been supported through inclusive classroom environments, appropriate seating arrangements, adaptive instructional strategies, simplified learning materials, individualized learning assistance, and emotional support. However, several challenges remain, including unequal classroom facilities, damaged learning equipment, and classroom conditions that have not fully supported the learning process. Educational fairness was reflected in equal learning opportunities, instructional adjustments based on students' needs, social support from teachers and peers, and the active participation of students with special needs in school activities. Nevertheless, several obstacles persisted, including excessive peer teasing, limited self-confidence among some students, and insufficient opportunities for individualized assistance.